Prevalence of asthma and its symptoms in Sri Lankan adults - K. D. Gunasekera; W. A. D. L. Amarasiri; U. C. M. Undugodage; H. K. M. S. Silva; A. Sadikeen; W. Gunasinghe; A. Fernando; B. P. R. Perera; A. R. Wickremasinghe (BMC, 2022)
Abstract Background Data on adult asthma is scarce in Sri Lanka. The objective of this study was to estimate the prevalence of asthma and its symptoms in adult Sri Lankans.  Methods A cross-sectional study using a translated version of the European Community Respiratory Health Survey screening questionnaire on subjects $$\ge$$ ≥ 18 years from 7 provinces in Sri Lanka was conducted. The asthma was defined as "wheezing in the past 12 months (current wheeze)", self-reported asthma attack in the past 12 months or on current asthma medication use. Results Among 1872 subjects (45.1% males, 48.8% between 18-44 years of age), the prevalence of current wheeze was 23.9% (95%CI: 22.0%-25.9%), self-reported asthma was 11.8% (95%CI: 10.3%-13.2%) and current asthma medication use was 11.1% (95% CI: 9.6%-12.5%). The prevalences were higher in adults > 44 years, 31.4% positively responded to any of the above questions (95%CI: 29.3%-33.4%) and 60.9% of current wheezers did not report having asthma whilst 38.2% used asthma medication. Among current wheezers, 80.1% had at least one other symptom, cough being the commonest. Those with no current wheeze, self-reported asthma and on current asthma medication use, 30%, 35.9% and 36.6%, respectively, reported at least one other symptom. Smokers comprises 22% current wheezers, 20.6% of self-reported asthmatics and 18.7% of current asthma medication users. Conclusions The prevalence of asthma in Sri Lankan adults is higher than the other South Asian countries and higher in the older age group. A significant percentage of symptomatic individuals did not report having asthma or being on medication.